IMPLEMENTASI PRINSIP EKONOMI ISLAM DALAM JUAL BELI ONLINE DENGAN SISTEM DROPSHIPPING - Muslimin, Fatkhul; Sulviana, Mita (Al-Maqashid: Journal of Economics and Islamic Business, 2023)
The aim of this research is to determine the application of Islamic economic principles in the online buying and selling of dropshipping systems carried out by PPTQ Al-Hasan Ponorogo students. This type of research for field research using qualitative methods. The techniques used in this study were interviews and documentation. After the data has been collected, it will be analyzed qualitatively descriptively. The results of this research include the following: 1) The application of Islamic economic principles has not been fully implemented well and female students have little understanding of Islamic economic principles and they do not know the principles of Islamic economics, 2) supporting factors make it easier for students to start an online business with a dropshipping system, they can start a business anywhere, it's easy to find consumers. The inhibiting factor is the limited operation of cellphones when you want to sell all the time, you don't know the stock of goods from consumers, 3) the impact of buying and selling online with the dropshipping system has two impacts, namely positive and negative